2021
DOI: 10.1177/09544089211037116
|View full text |Cite
|
Sign up to set email alerts
|

A review study on the performance of a parabolic trough receiver using twisted tape inserts

Abstract: Heat transfer in concentrating solar collectors like parabolic troughs has proven nowadays a very efficient method by using different passive techniques to increase the heat transfer rate. The use of passive techniques also increases the pumping power requirements to make the flow through the receiver. So, a number of researchers are working to find out the optimum performance conditions for parabolic trough receivers by using different types of inserts in flow paths. This paper presents a wide range of litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Further there are extensive review work has been reported to study the performance of SPT using twisted tape insert by different researchers. 28 S. Eiamsa-ard et al 29 conducted experimentation on heat transfer characteristics of receiver tube using a modification in twisted tape (alternate clockwise and counter clockwise arrangement) as shown in supplementary Figure 13. They concluded that, as compared to typical twisted tape this arrangement gives a 12.8-41.9% higher Nu and 12.5-41.5% more ff.…”
Section: Twisted Tapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further there are extensive review work has been reported to study the performance of SPT using twisted tape insert by different researchers. 28 S. Eiamsa-ard et al 29 conducted experimentation on heat transfer characteristics of receiver tube using a modification in twisted tape (alternate clockwise and counter clockwise arrangement) as shown in supplementary Figure 13. They concluded that, as compared to typical twisted tape this arrangement gives a 12.8-41.9% higher Nu and 12.5-41.5% more ff.…”
Section: Twisted Tapesmentioning
confidence: 99%
“…Further there are extensive review work has been reported to study the performance of SPT using twisted tape insert by different researchers. 28…”
Section: Artificial Roughness Techniquesmentioning
confidence: 99%
“…On the other hand, when attacking, it is helpful to do a v-cut (cutting/ability to change direction suddenly) to free himself from the opponent's guard. Applying several different training methods to provide a variety of exercises and avoid athlete saturation can be done to improve and develop an athlete's agility [13,14,15]. An athlete is expected to achieve optimal performance with excellent and varied training methods.…”
Section: Introductionmentioning
confidence: 99%
“…8 The other reason for its preference is it makes better use of direct radiation compared with other CST systems. 9 The solar thermal power plant can use a PTC in combination with fossil fuels as a backup when there is less availability of solar radiation. 3 The PTC is having a parabolic aperture to concentrates all solar radiation at focal point, due to which the temperature is raised up to 400 °C10 The parabolic trough is the most efficient thermal device in the mid-range of the temperature of 150-400°C, after this temperature the heat losses are also intended to increase.…”
Section: Introductionmentioning
confidence: 99%
“…8 The other reason for its preference is it makes better use of direct radiation compared with other CST systems. 9 The solar thermal power plant can use a PTC in combination with fossil fuels as a backup when there is less availability of solar radiation. 3…”
Section: Introductionmentioning
confidence: 99%